Precipitation and River Flow: Long‐Term Memory and Predictability of Extreme Events - Bunde, Armin; Bogachev, Mikhail I; Lennartz, Sabine (Extreme Events and Natural Hazards: The Complexity Perspective, 2012)
This chapter contains sections titled: Introduction Seasonal Detrending Linear Correlations Nonlinear Correlations and Multifractality Probability Density Function Hazard Function Prediction Algorithm and Efficiency Conclusion